"A comparative study of gender-based pay equity implementation: lessons for South Africa" - Mworia, Nkirote Kananu (Centre for Law and Society, 2026)
Discrimination is defined as "the practice of treating one person or group of people less fairly or less well than other people or groups .... " it is the "making or constituting of difference between". Even though it must be admitted that there are marked differences between men and women, discrimination has caused these differences to present women as being inferior to men, not exclusively, but especially in the workplace. This paper will look at some of the reasons why despite the almost universal acceptance of gender equality as a fundamental human right, women remain substantially disadvantaged in the workforce. Special emphasis will be in the context of significant pay disparities between men and women, and women's segregation into low status or marginal forms of work. However, in as much, as a whole paper could be written on the reasons for pay inequity and arguments for and against pay equity, the fact remains that pay inequity is a phenomenon which 21st Century women can no longer live with in the light of their role as wage earners for their families and active participants in their country's economies. As such, the more important study in my opinion, is how countries have sought to integrate pay equity into the fabric of their society. In an October 1997 report, the South African Breakwater Project which monitors employment equity in South Africa bi-annually, stated that: "Income distribution in South Africa ranks among the most unequal in the world". This could largely be attributed to the legacy of apartheid, that left the new South African government with many areas and levels of pay inequity to remedy. This may pose a danger to elimination of gender inequality that may easily be overshadowed by measures being taken to remedy racial inequality. It is my humble contention, that the two must go hand in hand with special emphasis being placed on the fate of the black woman. As a result, the comparative study of pay equity implementation in this paper is geared towards finding lessons to be learnt by South Africa as it embarks, with the Employment Equity Act 55 of 1998 newly in force, on a systematic elimination of discrimination in labor relations.